LETTER RECOGNITION AND HAND-COPYING SKILLS OF CHILDREN: A COMPARATIVE STUDY OF DARI AND ENGLISH ALPHABET LETTERS - Orfan, Sayeed Naqibullah; Timor, Mohammad Kazem (LLT Journal: A Journal on Language and Language Teaching, 2023)
This study aimed to explore and compare the difficulty level of alphabet letter recognition and hand-copying skills among children between two languages, English capital letters, and Dari alphabet letters. The participants were preschool children aged (4-5) in Taloqan City of Afghanistan. An observation method followed by a pre-test, a class session, and a post-test were conducted on the participants. The tests used in this study were Rapid Automatized Naming (RAN) and a paired samples t-test. The study's findings showed no significant difference in letter recognition between English and Dari letters; however, there was a significant difference in the hand-copying test. Also, the results of the study displayed that shapes of the letters played an important role in hand-copying the alphabet letters while it did not impact the letter recognition process.